Optimalisasi Pengambilan Keputusan dalam Perencanaan Pendidikan Islam Menuju Efektivitas Sistem Pendidikan Nasional - Sari, Desi Purnama; Oktavia, Wilni; Asmendri, Asmendri; Sari, Milya (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to explain how optimal decision-making can strengthen Islamic education planning and improve the effectiveness of the national education system. This study uses a descriptive-analytical approach by collecting data through literature studies on Islamic education planning theory, strategic management principles, and national education policy. The data obtained was analysed using content analysis techniques to identify patterns of ideas, conceptual consistency, and relevance to the current educational context. The results of the study show that the effectiveness of the national education system increases when planning is data-driven, aligned with spiritual values, and involves the participation of various stakeholders. Optimising decision-making requires collaboration between the government, educational institutions, and the community to ensure that Islamic education can contribute to the formation of superior and characterful individuals. This article recommends a participatory decision-making model that integrates theological, pedagogical, and sociological aspects to strengthen the quality and competitiveness of national education.